2016
DOI: 10.1007/s10551-016-3037-6
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Ethical Influences on the Work of Tax Practitioners

Abstract: As a contribution to the continuing debate about tax practitioner ethics, this paper explores the main streams of Western ethical thought that are relevant to tax practitioners' work, most typically deontology and consequentialism (although virtue ethics and distributive justice are also considered). It then goes on to consider the impact of such ethical influences on the professional ethical codes of conduct that govern tax practitioners' work (with specific reference to the UK and Ireland), and attempts to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…In contrast, the strategic choice of the taxpayer of our game payoff matrix in Table 4 shows that, armed with the information provided by the expert (TC), the MNCs are not deterred from venturing into abusive TP since it will give them the best outcome, slimmest chances of being caught and highest valued payoffs. This confirm arguments in the antecedence literature that accounting firms (TCs) belong to an elite profession whose services are mostly targeted and more beneficial to taxpayers against tax authorities (Killian & Doyle, 2004;Wurth & Braithwaite, 2016;Frecknall-hughes et al, 2017;Dienkowski & Peroni, 2016;Aksiana & Sujana, 2019). Therefore, no matter what the tax authority does, the best strategic option for the MNCs, from payoffs reported in Table 4, is to venture into abusive TP.…”
Section: Discussion Of Game Theoretic Outcomessupporting
confidence: 70%
“…In contrast, the strategic choice of the taxpayer of our game payoff matrix in Table 4 shows that, armed with the information provided by the expert (TC), the MNCs are not deterred from venturing into abusive TP since it will give them the best outcome, slimmest chances of being caught and highest valued payoffs. This confirm arguments in the antecedence literature that accounting firms (TCs) belong to an elite profession whose services are mostly targeted and more beneficial to taxpayers against tax authorities (Killian & Doyle, 2004;Wurth & Braithwaite, 2016;Frecknall-hughes et al, 2017;Dienkowski & Peroni, 2016;Aksiana & Sujana, 2019). Therefore, no matter what the tax authority does, the best strategic option for the MNCs, from payoffs reported in Table 4, is to venture into abusive TP.…”
Section: Discussion Of Game Theoretic Outcomessupporting
confidence: 70%
“…The Indonesian Journal of Accounting Research -Jan, Vol. 24 , No.1 , 2021 aggressive reporting (Blanthorne et al, 2013), a tax loophole (Sikka and Willmott, 2013), a tax audit (Alm and Torgler, 2011), tax alteration and tax fraud (Awang and Amran, 2014), technical competence (Frecknall et al, 2016), public responsibility and interest (Doyle et al, 2009), and so forth. The theory of Allingham and Sandmo (1972) stated that no individuals are willing to pay taxes; they will always be against it.…”
Section: Ethics and Ethical Issuesmentioning
confidence: 99%
“…Bishop (2013) revealed that in the 21st-century, ethics failures have happened in business industries. Frecknall et al (2016) also stated that the international media announced a massive number of tax practitioners that behave unethically in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been previous studies that examined the CMD of tax practitioners (Frecknall-Hughes et al, 2017), to the best of our knowledge, our study is one of the first that attempts to understand the effects of length of service on CMD and ethical intention among public sector auditors. Additionally, we believe it to be the first study to examine such issues in Latin America.…”
Section: Introductionmentioning
confidence: 99%